Development Diastolic Dysfunction Myocardium in Children with Acute Lymphoblastic Leukemia at the Stages of fhe Polychemotherapy - A. A. Savisko; A. V. Shestopalov; E. D. Tepljakova; K. S. Aslanyan; N. E. Tarasova; S. P. Parmon (Медицинский вестник Юга России, 2010)
The development of progressive myocardial dysfunction is one of the side effects of polychemotherapy. Changes in diastolic filling of the left ventricular is the earliest marker that precedes the full-scaled clinical picture of heart failure. Purpose: Assessment of left ventricle’s diastolic function and the study of the state of lipid peroxidation processes in children with acute leukemia at the stages of polychemotherapy. Materials and Methods: We have examined 54 patients with acute lymphoblastic leukemia at the age ranging from 3 to 17 years old. Results: Complex transthoracic Doppler echocardiography shows the occurrence of diastolic dysfunction at the time when the disease is diagnosed and its progression after the end of polychemotherapy. The development of cardiac complications is accompanied by an increase in the generation of reactive oxygen species, accumulation of oxydated lipoproteins, which suggests the free-radical genesis of myocardial damage. Summary: Early detection of disorder of diastolic function of the left ventricle may allow to appoint cardiotropic therapy on the initial stage and decrease the rate of complications of polychemotherapy.